1995
DOI: 10.1007/bf02540988
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the resolution of individualtrans‐18:1 isomers by capillary gas‐liquid chromatography: Use of a 100‐m CP‐Sil 88 column

Abstract: Doubling the length of a CP-Sil 88 capillary column (Chrompack, Middelburg, The Netherlands) from 50 to 100 m remarkably improves the resolution of individual trans-18:1 isomers from either ruminant fats or partially hydrogenated oils. Although the use of a 50-m column gives interesting results, it does not allow sufficient resolution of the trans-10 and trans-11 18:1 isomers. Moreover, the trans-6 to trans-9 18:1 isomers emerge as a single group of peaks, whereas the trans-12 isomer is only partly resolved fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 16 publications
3
62
0
2
Order By: Relevance
“…3 are similar to the findings of a previous report 2, 19,20 . These orders are affected by the GC temperature.…”
Section: Elution Order Of Cis-and Trans-c18:1-me Isomers Atsupporting
confidence: 92%
See 1 more Smart Citation
“…3 are similar to the findings of a previous report 2, 19,20 . These orders are affected by the GC temperature.…”
Section: Elution Order Of Cis-and Trans-c18:1-me Isomers Atsupporting
confidence: 92%
“…For example, the fatty acid content of cis-4-C18:1 and cis-5-C18:1 isomers was 0.21 g per 100 g oil, while that of cis-6-C18:1, cis-7-C18:1, and cis-8-C18:1 isomers was 2.44 g per 100 g oil in PHVO Table 4 . Previous studies reported that minor cis-C18:1 isomers ranging from cis-6 to cis-15 except cis-9 exist in PHVO and milk fat 4, 14,19 . The cis-C18:1 and trans-C18:1 isomer peaks overlapped.…”
Section: Contents Of Cis-and Trans-c18:1 Isomers In Edible Fats and Oilsmentioning
confidence: 94%
“…Individual FAMEs were identified by comparison to a standards mixture of 37 Component FAME Mix (Supelco, Bellefonte PA, USA). The identification of isomers of C18:1 was based on commercial standard mixtures (Supelco, Bellefonte PA, USA) and published isomeric profiles (Wolf & Bayard, 1995). All methods using peak normalisation and which express the results in relative percentages of the area of the analysed peaks are subject to overestimation because the areas of small peaks are not considered.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that GC column efficiency is proportional to the square root of column length and the resolution is strongly influenced by the selectivity, therefore increasing column length will lead to appreciably higher resolution, and selectivity modification will affect significantly separation as well [12,30]. For instance, during the 1970's, the use of polar packed columns (such as SP-2340 or OV-275) did not afford separation of cis-18:1 fatty acids from trans-18:1 isomers, and even poorer quantitation of each of the positional isomers [13,23].…”
Section: Direct Gas Chromatographymentioning
confidence: 99%